Physicochemical characteristic of chicken sausage substituting tapioca flour with sorghum seed flour (Sorghum Bicolor L. Moench): Physicochemical Properties of Sorghum-Substituted Chicken Sausage - Muhammad Zahir Afif; Muhammad Fabian Prayustio; Mulia Winirsya Apriliyani; premy rahayu (Talenta Publisher, 2026)
Chicken sausage is a widely consumed processed meat product due to its high protein content, desirable texture, and affordability. Its formulation generally involves meat proteins, carbohydrate-based fillers, and functional additives. Proteins act as structural stabilizers of emulsions, while fillers such as tapioca flour improve texture, water retention, and yield. However, tapioca flour has relatively low fiber compared to sorghum flour. Germinated sorghum (Sorghum bicolor L. Moench) contains 6.82% protein, 1.81% fat, 2.21% crude fiber, and 77.47% carbohydrates, with enhanced nutritional quality compared to ungerminated grains. This study aimed to evaluate the chemical and physical characteristics of chicken sausage with partial substitution of tapioca flour by germinated sorghum flour, focusing on protein, fat, moisture, crude fiber, texture, Water Holding Capacity (WHC), cooking loss, and L*a*b* color parameters. The experiment used a Completely Randomized Design (CRD) with five substitution levels (0%, 5%, 10%, 15%, and 20%) and four replications. Results showed that sorghum substitution significantly increased protein and crude fiber content, affected fat levels, but did not alter moisture. In terms of functional properties, germinated sorghum flour had a highly significant effect on WHC, texture, cooking loss, and color analysis. Sausage with 50% sorghum flour and 50% tapioca flour produced the best balance, yielding higher WHC, lower cooking loss, acceptable texture, and balanced color. Overall, germinated sorghum flour is a promising alternative filler to improve both nutritional and functional qualities of chicken sausage.